Case Report: A Case With MOGAD and Anti-NMDAR Encephalitis Overlapping Syndrome Mimicing Radiological Characteristics of CLIPPERS - Guo, Jia; Bu, Yujie; Liu, Wei (Frontiers in Immunology, 2022)
Herein, we reported a case of a young man diagnosed with MNOS (anti-myelin oligodendrocyte glycoprotein associated disease (MOGAD) and anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis overlapping syndrome, i.e., MNOS), whose imaging findings in magnetic resonance imaging (MRI) mimicked chronic lymphocytic inflammation with pontine perivascular enhancement responsive to steroids (CLIPPERS). We reported a case of refractory anti-NMDAR encephalitis that recurred after standard first-line and second-line treatment. The patient presented with CLIPPERS on imaging at recent hospital admission, and his MOG antibodies were seropositive. After intravenous methylprednisolone (IVMP) treatment, the patient’s symptoms were significantly alleviated. In this case, we demonstrated that MNOS could mimic the radiological characteristics of CLIPPERS. Future studies should focus on the diagnosis and treatment of antibody overlap syndrome.